Perceptions of Indonesian Students on the Role of Teachers in Offline and Online Learning During the Covid-19 Pandemic Period - Alhamuddin, Alhamuddin; Zebua, Rony Sandra Yofa (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aimed to analyze student perceptions regarding the role of teachers in classroom learning compared to online learning during the Covid-19 pandemic by applying a quantitative approach with a survey method. Population in this study was students throughout Indonesia who were actively learning during the Covid-19 pandemic.Â The research used Cluster Sampling technique by distributing online forms to students studying at home in all provinces in Indonesia, from Aceh to Papua; while sampling was conducted by random system. Chi square data analysis was carried out to analyze the close relationship between two variables that had nominal data. The results showed that almost all respondents (683 students or 93.8% of them) preferred face-to-face learning with teachers, while a small portion of 45 respondents (6.2%) liked face-to-screen learning (online). Out of 728 respondents, 647 students (88.9%) thought that the teacher’s role could not be replaced by technology, and 81 students (11.1%) thought that the teacher’s role could be replaced by technology. Thus, it can be concluded that most students in Indonesia still preferred face-to-face learning in class. Inequality in the distribution of learning resources such as internet network and teacher competence became a major problem in online learning, especially for students who lived in rural and disadvantaged areas.